Antarctica on the International Court of Justice: 60 year after the cases Union Kingdom v. Chile and Union Kingdom v. Argentina - Ferrada Walker, Luis Valentín (Universidad de Chile. Facultad de Derecho, 2015)
The applications presented in relation with the sovereignty over the Antarctica by the United Kingdom on International Court of Justice against Chile and against Argentina in 1955 are analyzed. The documents delivered during the process are also revised. The defendants States were not prepared to accept the Court jurisdiction; therefore both causes were definitely retired from the list without resolve about the dispute. Nevertheless, it seems relevant to consider these cases to know the grounds on which the implicated States and specially the United Kingdom support their Antarctic sovereignty and also to understand that at the end the Chilean and Argentinian attitude helped on the process that will finish few years later with the signature of the Antarctic Treaty. Se analizan las demandas respecto a la soberanía sobre la Antártica presentadas por el Reino Unido ante la Corte Internacional de Justicia contra Chile y contra Argentina en 1955. Se revisan también los documentos emitidos durante la tramitación de estas causas. Los Estados demandados no estuvieron dispuestos a otorgar competencia a la Corte, motivo por el cual ambas causas fueron en definitiva retiradas de la lista sin que se resolviera sobre el fondo de la disputa. No obstante ello, parece relevante considerar estos casos para conocer los fundamentos en que los Estados implicados, y en especial el Reino Unido, basan su soberanía antártica, así como para comprender que, en definitiva, la actitud de Chile y Argentina colaboró en el proceso que culminaría pocos años más tarde con la firma del Tratado Antártico.